Does Banking Waiver Help SMEs to Survive during the Pandemic? The Role of Innovative Financial Practices - Kurniawan Kurniawan (Jurnal Keuangan dan Perbankan, 2023)
This research aims to examine the effect of policy-related factors in the form of banking waivers on the sustainable financial performance and survival-recovery of SMEs during the Covid-19 Pandemic. Besides, this research also highlighted whether the innovative financial practice has a mediating effect on the relationship between sustainable financial performance and the survival recovery of SMEs. The third edition of SMARTPLS software was used for the PLS-SEM analysis of the data. Purposive sampling was used to choose and collect samples using predetermined criteria implemented online and offline. A total of 1026 SMEs who met the eligibility criteria participated in the survey. Most respondents are based in the West Java Province of Indonesia, spread over several cities. The findings show that banking waivers provided by the Indonesian government positively affect the sustainable financial performance of SMEs, which in the end help them to survive and recover their business during the pandemic crisis. The innovative financial practices by SMEs have also proven to strengthen the positive effect of sustainable financial performance on their survival-recovery amid the pandemic crisis.